Characteristics of joint displays illustrating data integration in mixed‐methods nursing studies. (25th November 2019) - Younas, Ahtisham; Pedersen, Maria; Durante, Angela
Abstract: Aims: To identify the characteristics of joint displays illustrating the data integration in mixed‐methods nursing studies and to make recommendations for effective use of joint displays for the integration of qualitative and quantitative data in mixed‐methods studies. Design: Discussion Paper. Data Sources: We have completed this paper as a part of a mixed‐methods prevalence review of 190 studies published in nursing journals. We searched 10 nursing journals and three databases from January 2014–April 2018, additional journal search was performed from May–September 2018. We reviewed 17 studies that used joint displays as the method of data integration. Using a joint display typology, checklists, summary tables, and personal experiences of using joint displays, we evaluated the quality of displays. Implications for Nursing: Nurse researchers should use advanced data integration approaches to increase the rigour of the mixed‐methods studies. Joint displays can enable nurse researchers to efficiently integrate and synthesize the qualitative and quantitative data in mixed‐methods studies. However, nurse researchers should clearly label the type and title of the display, include both qualitative and quantitative data and interpretations, and highlight the mixed‐methods interpretations as confirmed, divergent, or expanded in the displays. Conclusion: Joint displays are adopted for data integration in nursing mixed‐methods studies. Improvements are required concerning data presentation in the displays. Researchers should provide clear titles and supporting data and inferences and identify the meta‐inferences by assessing the fit between quantitative and qualitative data. Impact: Despite the importance of integration in mixed methods, reviews indicated a consistent lack of integration in nursing research. Joint displays are structured frameworks used for the integration and synthesis of the qualitative and quantitative data at the analysis and interpretation levels. The discussed typology and characteristics of displays can enable nurse researchers to enhance the quality and presentation of integrated results in mixed‐methods studies. Abstract : 目的: 明确混合方法护理研究中数据整合的联合显示特点, 为混合方法护理研究中定性和定量数据整合的联合显示的有效使用提出建议。 设计: 讨论论文。 数据来源: 我们完成了这篇论文, 对190项发表在护理期刊上的研究进行了患病率评估。我们从2014年1月至2018年4月检索了10份护理期刊和3个数据库, 从2018年5月至9月还进行了期刊检索。我们研究了17项使用联合显示作为数据集成方法的研究。使用联合显示类型、检查表、摘要表和个人使用联合显示的经验, 我们评估了显示的质量。 护理启示: 护士研究者应采用先进的数据整合方法, 提高混合方法研究的严谨性。联合显示可以使护士研究者有效地整合和综合混合方法研究中的定性和定量数据。然而, 护士研究者应该清楚地标注显示的类型和标题, 包括定性和定量数据和解释, 并强调显示中的确认、分歧或扩展的混合方法解释。 结论: 护理混合方法研究采用联合显示进行数据整合。需要改进显示器中的数据显示。研究者应提供明确的标题和支持性数据和推论, 并通过评估定量和定性数据之间的匹配度来确定元推论。 影响: 尽管在混合方法中整合非常重要, 但是以往研究表明在护理研究中整合的持续缺乏。联合显示是一种结构化框架, 用于在分析和解释层面上整合和综合定性和定量数据。讨论显示的类型和特性可以使护士研究人员在混合方法研究中提高整合结果的质量和表达方式。